The Tradition Of Tattooing As A Symbol Of Social Status In The Dayak Ngaju Tribe Of Central Kalimantan - Basori, Muhamad Hasan; Umami, Zahrotul; Novianur, Fathul Ramadan (Borobudur Communication Review, 2025)
Traditional tattoo is recognized as a cultural heritage and a means of emotional, social, and symbolic expression. Furthermore, the images or motifs used in the tattoos are sometimes only understood by the owner or the person who created them. For indigenous tribes, tattoos are considered sacred, possessing a religious nature, and there are traditional tattoos that not everyone is permitted to have. This study aims to analyze the symbolic meaning of traditional tattoo art within the social life context of the Dayak Ngaju Tribe, utilizing the theoretical framework of symbolic interactionism by George Herbert Mead. Through a qualitative method involving observation, interviews, and literature review, the research concludes that Dayak Ngaju tattoos primarily function as Indicators of social status, representations of life history, Manifestations of spiritual power. The visual motifs inscribed on the body possess encrypted meanings exclusive to the Dayak Ngaju community. Moreover, the tattoos act as a medium for nonverbal communication that strengthens the bond between the individual and their ancestral entities, proving the essential role of visual symbols in the articulation of identity and social meaning.